Overview of Elderly Visit to Posyandu Reviewed From Senior Education in Sidoarjo: Tinjauan Kunjungan Lansia ke Posyandu Ditinjau Dari Pendidikan Senior di Sidoarjo - Ananda, Selvie; Purwanti, Yanik (Indonesian Journal of Innovation Studies, 2020)
The Elderly Posyandu is an Integrated Service Post for the elderly in a certain area. Reports from Elly's research data in Sukodono village - Sidoarjo in 2014 that participated in the elderly posyandu obtained 50% of the 70% target. For this reason, it is very interesting to conduct a study again which aims to find out the description of elderly visits to posyandu in terms of elderly education. The research design used was descriptive without statistical tests with a total population of 15 respondents overall aged 45 years which was conducted in August 2019 at Tanggulangin Asri RT 01 RW 06 Tanggulangin Village, Sidoarjo. The study used secondary data by recording the format for tracing educational data and elderly visits in the register book. The data were analyzed descriptively using frequency and percentage tables as well as cross tables. The results showed that the elderly who actively visited the posyandu for the elderly were high school (23.1%) while the elderly who did not actively attend the elderly visits had more elementary education (100%). and Universities (100%). So it can be said that most (80%) elderly are not active in attending elderly visits. So it is advisable for health workers to provide information about the importance of screening in the elderly.